THE DETERMINANT FACTORS OF TELEVISION’S AUDIENCE IN CHOOSING TV CHANNEL IN THE DISRUPTIVE ERA - Rendra Widyatama; Suranto AW; Maizatul Haizan Mahbob (Profetik: Jurnal Komunikasi, 2021)
This qualitative research article aims to explain the determinant factors that influence viewers to choose TV's channels in the disruptive era. In the period triggered by the increase of the internet and digital technology, many innovations emerged, potentially disturbing and destroying the old system. Loyalty in the broadcasting industry of the disruptive age is temporary and can change quickly. Viewers effortlessly change their TV channels according to their interests and desires. Therefore, TV managers have to pay attention to various factors on TV's audience to choose TV channels. These determinant factors occupy a prominent position among TV station managers in Indonesia and around the globe as an essential contrive to grab the attention of TV viewers. Primary data was dig using the focus group discussion (FGD) before the Covid-19 pandemic occurred. The authors conducted five FGDs involving 9-12 participants in each FGD. This research found that there are 23 determinant factors influencing audience in choosing TV channels in the disruptive era. The 23 factors are divided into four categories namely, TV program content, audience's purposes, corporate action, and community influence. The conclusion is, from four determinants factors, the range of TV content comprises the most varied category. In contrast, community influence factor occupies the last position with one variation.